COMPUTER MODELS OF NAVIGATION AIDS FOR MOBILE ROBOTS - Mykhaylov, Evgeniy; Lingur, Valeriy; Vudvud, Alexander; Yarovy, Artem (European Science, 2025)
An analysis of individual features of mobile robot navigation was carried out, which can be used to develop algorithms for checking robot movements. The capabilities of computer modeling were expanded using the method of studying algorithms and ensuring t